Medical sociology - Cockerham, William C. (Upper Saddle River, N.J. : Prentice Hall, 2010)
SOC 3343.
Medical sociology -- Epidemiology -- Social demography of health : social class -- The social demography of health : gender, age, and race -- Social stress and health -- Health behavior and lifestyles -- Illness behavior -- The sick role -- Doctor-patient interaction -- Healing options -- Physicians -- The physician in a changing society -- Nurses, physician assistants, pharmacists, and midwives -- The hospital in society -- Health care delivery and social policy in the United States -- Global health care.
Includes bibliographical references (p. 367-403) and indexes.
Keywords: Social medicine